2013
DOI: 10.1007/jhep09(2013)088
|View full text |Cite
|
Sign up to set email alerts
|

Double scaling in tensor models with a quartic interaction

Abstract: In this paper we identify and analyze in detail the subleading contributions in the 1/N expansion of random tensors, in the simple case of a quartically interacting model. The leading order for this 1/N expansion is made of graphs, called melons, which are dual to particular triangulations of the D-dimensional sphere, closely related to the "stacked" triangulations. For D < 6 the subleading behavior is governed by a larger family of graphs, hereafter called cherry trees, which are also dual to the D-dimensiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 132 publications
(212 reference statements)
2
87
0
Order By: Relevance
“…In particular, 2 Given a beta function βg = µ∂µg(µ), we can linearize it around a fixed point at g * : the RG will give meaningful results for the scaling exponent of the double-scaling limit even in cases where the expression for the partition function does not converge. In higher dimensions, there are indications that the partition function is summable in the double-scaling limit [20][21][22] and contributions from higher orders in the 1/N expansion [23] can be retained consistently. The FRG allows us to access tensor models corresponding to d = 4 dimensions, where other methods that work successfully in the matrix-model case, break down.…”
Section: A Renormalization Group and Double-scaling Limitmentioning
confidence: 99%
“…In particular, 2 Given a beta function βg = µ∂µg(µ), we can linearize it around a fixed point at g * : the RG will give meaningful results for the scaling exponent of the double-scaling limit even in cases where the expression for the partition function does not converge. In higher dimensions, there are indications that the partition function is summable in the double-scaling limit [20][21][22] and contributions from higher orders in the 1/N expansion [23] can be retained consistently. The FRG allows us to access tensor models corresponding to d = 4 dimensions, where other methods that work successfully in the matrix-model case, break down.…”
Section: A Renormalization Group and Double-scaling Limitmentioning
confidence: 99%
“…Then the analyticity domain of A G extends to (61). The fact that the domain extends under the assumption (d) has a consequence for the same study now under the conditions (a) and (e).…”
Section: Theorem 1 (Extended Domain Of Analyticity) Consider a Tensomentioning
confidence: 70%
“…It is shown that the colored tensor models admit a large N expansion and the leading contributions represent higher dimensional sphere [26,27]. Moreover, it is claimed that one can take a double scaling limit in the tensor models [28,29]. Thus, the colored tensor models give a fascinating formulation of higher dimensional quantum gravity.…”
Section: Jhep07(2015)088mentioning
confidence: 99%